Tropomyosin is required for cardiac morphogenesis, myofibril assembly, and formation of adherens junctions in the developing mouse embryo. Issue 6 (24th February 2014) - McKeown, Caroline R.; Nowak, Roberta B.; Gokhin, David S.; Fowler, Velia M.
<x xml:space="preserve">Abstract</x> BACKGROUND: We explored a function for tropomyosin (TM) in mammalian myofibril assembly and cardiac development by analyzing a deletion in the mouse TPM1 gene targeting αTM1, the major striated muscle TM isoform. RESULTS: Mice lacking αTM1 are embryonic lethal at E9.5 with enlarged, misshapen, and non‐beating hearts characterized by an abnormally thin myocardium and reduced trabeculae. αTM1‐deficient cardiomyocytes do not assemble striated myofibrils, instead displaying aberrant non‐striated F‐actin fibrils with α‐actinin puncta dispersed irregularly along their lengths. αTM1's binding partner, tropomodulin1 (Tmod1), is also disorganized, and both myomesin‐containing thick filaments as well as titin Z1Z2 fail to assemble in a striated pattern. Adherens junctions are reduced in size in αTM1‐deficient cardiomyocytes, α‐actinin/F‐actin adherens belts fail to assemble at apical cell–cell contacts, and cell contours are highly irregular, resulting in abnormal cell shapes and a highly folded cardiac surface. In addition, Tmod1‐deficient cardiomyocytes exhibit failure of α‐actinin/F‐actin adherens belt assembly. CONCLUSIONS: Absence of αTM1 resulting in unstable F‐actin may preclude sarcomere formation and/or lead to degeneration of partially assembled sarcomeres due to unregulated actomyosin interactions. Our data also identify a novel αTM1/Tmod1‐based pathway stabilizing F‐actin at cell–cell junctions, which may be required for maintenance of cell shapes during embryonic cardiac morphogenesis. Developmental Dynamics 243:800–817, 2014. © 2014 Wiley Periodicals, Inc.